The Study of Learning Outcomes under Thai Qualifications Frameworks for Higher Education (TQF: HEd) in Community Health Nursing Practicum Course of 4th Year Students, Faculty of Nursing, Naresuan University - Amaraporn Puraya; Somsak Thojampa; Srisupha Jaisopha (Universitas Airlangga, 2020)
Introduction: This was descriptive research which aimed to study the learning outcomes based on the Thai Qualifications Frameworks for Higher Education (TQF: HEd)) after completing community health nursing practicum of 4th year students, the Faculty of Nursing, Naresuan University.Methods: The samples were 113 4th year nursing students. Data were collected using the evaluation form of opinions on learning outcomes in six areas, namely morals and ethics, knowledge, intellectual skills, interpersonal skills and responsibility, numerical analysis, communication and information technology skills and professional practice skills. Data were analyzed using frequency distribution, percentage, mean and standard deviation.Results: The research results showed that the mean score of the opinions of the 4th year students, Faculty of Nursing, Naresuan University, toward their learning outcomes based on the TQF: HEd was quite high in all six areas. The overall score was at a high level (X̄=4.36, S.D. =0.42). The area with the highest level was morals and ethics (X̄ = 4.50, S.D = 0.39), followed by professional practice skills (X̄ = 4.48, S.D. = 0.49), interpersonal skills and responsibility (X̄ = 4.43, S.D. = 0.53), numerical analysis, communication and information technology skills (X̄ = 4.31, S.D. = 0.55), intellectual skills (X̄= 4.31, S.D. = 0.52) and knowledge (X̄ = 4.11, S.D. = 0.55), respectively.Conclusion: The research results can be used as the guidelines for the development of learning outcomes and assessment in accordance with the TQF: HEd.